How Competition Delivers Positive Results in Transport : A Case Study - de Rus, Ginés (World Bank, Washington, DC, 2012)
In this case study the government is initially the monopoly supplier of travel and freight service - by ferry, jetfoil, and airplane - between two islands. It then allows private operators to enter the industry. The first new operator revolutionizes the market, setting off a chain of events that lead to a fall in prices, enormous growth in the market, more varied and attractive services for passengers, and more efficient freight services for business. The experience shows both the dramatic effect of removing barriers to entry by new firms and how the different values consumers place on different kinds of travel time can create market opportunities not foreseen in the typical demand elasticities used by policy planners and forecasters.